2014
DOI: 10.1152/japplphysiol.00893.2013
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction affects dynamic cerebral autoregulation during Valsalva maneuver: comparison between healthy and autonomic dysfunction subjects

Abstract: The role of autonomic nervous system (ANS) in adapting cerebral blood flow (CBF) to arterial blood pressure (ABP) fluctuations [cerebral autoregulation (CA)] is still controversial. We aimed to study the repercussion of autonomic failure (AF) on dynamic CA during the Valsalva maneuver (VM). Eight AF subjects with familial amyloidotic polineuropahty (FAP) were compared with eight healthy controls. ABP and CBF velocity (CBFV) were measured continuously with Finapres and transcranial Doppler, respectively. Cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 60 publications
1
35
1
Order By: Relevance
“…Dynamic cerebral autoregulation using transfer function analysis has been widely studied in cerebrovascular disease [911,15,16,2330]. Lower phase shift, reflecting less effective autoregulation, has been demonstrated in poorly compensated carotid or MCA stenosis [27,29, 30] or vasospasm after subarachnoid hemorrhage [27,28] as well as in ischemic stroke [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic cerebral autoregulation using transfer function analysis has been widely studied in cerebrovascular disease [911,15,16,2330]. Lower phase shift, reflecting less effective autoregulation, has been demonstrated in poorly compensated carotid or MCA stenosis [27,29, 30] or vasospasm after subarachnoid hemorrhage [27,28] as well as in ischemic stroke [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic cerebral autoregulation (CA) can be rapidly and noninvasively assessed at the bedside by transfer function analysis (TFA) between spontaneous oscillations in blood pressure and cerebral blood flow velocity [914]. There is an overall agreement that dynamic CA is impaired in acute IS [15,16] but its relationship with HT or CE is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations (3,6,(35)(36)(37) reported that dynamic CA is unlikely to be constant and is altered by a change in cerebral vascular condition. For example, hypercapnia-induced cerebral vasodilation attenuates dynamic CA, while hypocapnia-induced cerebral vasoconstriction enhances dynamic CA (1).…”
mentioning
confidence: 91%
“…Frequently volunteers blinked their eyes, thereby causing artifacts in the REG signal. Inconsequential changes observed during Valsalva maneuver may have been caused by autonomic dysfunction, previously described by Castro [18].…”
Section: Regmentioning
confidence: 68%
“…During turning of the titling table, large artifacts in the signal occurred at the beginning and end of the tests. This multiphase reaction may reflect orthostatic intolerance, caused by complex interactions of central and peripheral cardiovascular control [18].…”
Section: Tcd and Nirsmentioning
confidence: 99%